Isolation, Identification and Bioactivity of Natural Products from Melaleuca Cajuputi (Myrtacea) - Ul Hassan, Vaqar (1996)
In this study the components of aerial and subterranean parts of Melaleuca cajuputi were isolated and identified. Chemical investigation on the leaves resulted in the isolation of two known triterpenoids, betulinic acid and u rsolic acid ester. The oily fractions contained two phenolic components, a naphthalene dione, an anthracene carboxal-dehyde and a phenenthracene analogy. Methanol extracts of the bark, seeds, and flowers allowed for the isolation and identification of betulinic acid, urolic acid and betuline, respectively. Their structures were determined using m odern spectroscopic techniques such as IR, NMR, MS and by comparison with literature.The bioassay was carried out on crude extracts of leaves, roots, seeds, and bark against first in star mosquito larvae (Aedes albopictus) according to the procedure described in the literature. These extracts were found to be acute or relatively toxic to the target organisms. Extract from leaves exhibited the highest toxicity followed by extracts from roots, seeds, and bark respectively.